The Association between Parenting Behavior and Executive Functioning in Children and Young Adolescents - Sosic-Vasic, Zrinka; Kröner, Julia; Schneider, Sibylle; Vasic, Nenad; Spitzer, Manfred; Streb, Judith (Frontiers in Psychology, 2017)
Executive functioning (EF) is associated with various aspects of school achievement and cognitive development in children and adolescents. There has been substantial research investigating associations between EF and other factors in young children, such as support processes and parenting, but less research has been conducted about external factors relating to EF in older children and adolescents. Therefore, the present study investigates one possible factor that could correlate with EF in school-age children and adolescents: parenting behavior. The cross-sectional study design gathered data from 169 children in primary schools, middle-schools, and Gymnasien, and their corresponding parents. All children underwent a standardized task to measure EF, the computer-based Erikson Flanker task, which evaluates EF as a function of error rates and response time. A self-report questionnaire was used to assess parenting behavior. Multilevel analysis was implemented to test the effects of parenting behavior on EF in school-age children. The results show significant associations between various parenting behaviors and children’s EF: High scores on parental involvement or parental responsibility are associated with low error rates on the Erikson Flanker task, whereas high parental scores on inconsistent discipline are associated with high error rates. These correlations between parenting behavior and EF remained significant despite controlling for child age, maternal education, family income, and baseline performance (i.e., congruent trials on the Erikson Flanker task). No associations were found between parental behavior and reaction time on the Erikson Flanker task. These results indicate the important association between parenting behaviors and EF skills in school-age children, and foster the necessity to inform parents about ways in which they can optimally support their children’s cognitive development.